A visco-hyperelastic model for hydrogels with tunable water content. (April 2023) - Zhong, Danming; Xiang, Yuhai; Wang, Zhicheng; Chen, Zhe; Liu, Junjie; Wu, Zi Liang; Xiao, Rui; Qu, Shaoxing; Yang, Wei
Abstract: Hydrogels without special treatment would lose water dramatically, which significantly alters their properties. No physically-based constitutive models have been developed so far to quantify the evolution of visco-hyperelastic responses with water content of hydrogels. In this work, systematical experiments are performed on polyacrylamide (PAAm) hydrogels with varied water content. The results reveal that the increase of modulus caused by deswelling is much more pronounced than the decrease of modulus caused by swelling. A more significant strain-softening phenomenon and a transition from almost pure hyperelastic behaviors to apparent viscoelastic behaviors are observed as the water content decreases. To fully capture the experimental observations, a micromechanical model is developed. In this model, the rate-independent hyperelastic response comes from the contributions of both cross-linked networks and entanglements, while the rate-dependent viscoelastic response arises from the reptation of free chains. The relations between model parameters (e.g., cross-linked shear modulus, entangled shear modulus, and relaxation time) and water content are further derived using the scaling law in polymer physics. The developed visco-hyperelastic model exhibits remarkable prediction ability for PAAm hydrogels with a wide water content distribution. The finite element analysis also verifies that the model can describe the mechanical responses of hydrogels in complex loading conditions. The current work deepens our fundamental understanding on the effect of water content on mechanical behaviors of hydrogels. It also provides an efficient theoretical framework to predict the performance of hydrogels in practical applications.